Developing a model of patient values in medical decision making: A qualitative inquiry into insulin initiation in type 2 diabetes / Lee Yew Kong - Lee, Yew Kong (2014)
Developing a model of patient values in medical decision making: A qualitative inquiry into insulin initiation in type 2 diabetes Background: Shared decision making (SDM) is a medical decision making model where at least two parties (for example, patient and doctor) share information and values in order to build consensus on the preferred treatment to implement. Patient values are the most mentioned element in definitions of SDM. However, there is no agreed definition of patient values in both SDM and the larger field of medical decision making. Therefore, this study aimed to develop a model of patient values using insulin initiation in type 2 diabetes as an exemplar. Methods: The study design was a qualitative study based on an interpretive descriptive approach. Data was collected from both healthcare professionals (HCPs) and patients. The conceptual frameworks used were the Ottawa Decision Support Framework and Schwartz’s theory of values. Purposive sampling was used to recruit HCPs involved in insulin initiation and patients who were deciding about insulin. Participants were recruited from the three main healthcare settings in Malaysia (public health clinics, public university-based primary care clinics, and private clinics). An interview topic guide was developed based on the conceptual frameworks and expert opinion. In-depth interviews and focus group discussions were conducted between January 2011 and June 2012. Interviews were stopped when data saturation was achieved. The interviews were transcribed verbatim and managed with Nvivo9 software. Data was analysed using thematic analysis and Strauss’ method of coding. A process of open, selective and axial coding was used to develop the model of patient values. Results: Forty-one HCPs were interviewed (30-66 years old; females, n=31). The sample was diverse in terms of professional background (general practitioners, medical officers, family medicine specialists, government policy makers, diabetes nurse educators, endocrinologists and pharmacists), healthcare settings (public, private) and ethnicity (Malays, Chinese, Indians, other ethnicities). Twenty-one patients were interviewed (28-67 years old; males, n=12) from diverse healthcare settings and ethnic backgrounds. Based on HCP interviews, barriers and facilitators to insulin initiation included patient barriers (e.g. injection-related barriers, insulin-related barriers, social factors, emotional barriers), HCP barriers (e.g. lack of HCP motivation and confidence, lack of training, conflicting advice between HCPs), and system-related barriers. These factors provided the psychosocial and cultural context in which patient values were explored. Based on patient interviews, the types of patient values during insulin initiation were identified. Three categories of values emerged: (1) positive and negative insulin-specific beliefs, (2) personal life goals (e.g. health, career, finance) and philosophies (e.g. avoiding suffering, fatalism, not being a burden), and (3) socio-cultural values (e.g. religious teachings, cultural practices) and family background. A model of patient values was then developed based on the three categories. Conclusions: When supporting patients in decision making, HCPs need to address more than just treatment-specific beliefs. A deeper understanding of patients’ life priorities and socio-cultural background are essential, as these also influence decisions about treatments. The proposed model of patient values helps to clarify the definition of patient values in SDM and can be used to systematically explore patient values during consultations.